Knowledge and awareness on landslides among teachers in northern area of Malaysia - Ahmad, Jamilah; Lateh, Habibah (Public Works Department Malaysia, 2015)
Cases of landslides in Malaysia did not only destroy properties but have also taken the lives of people. The society need to be educated about the danger of landslides, so that, they can be better prepared to face the disaster that can happen at any time. One of the main groups that need to be educated on the danger of landslides are teachers. Teachers teach students the importance of maintaining and conserving the environment, as well as the basics about landslides including early signs of landslides and causes of landslides. In order to disseminate knowledge about landslides accurately to students, teachers themselves need to first, be knowledgeable on the subject matter. This research has two objectives, first, to identify the level of knowledge and awareness regarding landslides among teachers; second, to investigate the differences in knowledge and awareness regarding landslides between teachers who teach in landslide prone areas with teachers who teach in non-landslide prone areas. This research used qualitative method through in-depth interview to gather information from 10 teacher respondents who are teaching in the Northern region of Malaysia. The findings show that the level of landslides knowledge and awareness among teachers is high. The findings also indicate that there is no difference in term of landslides knowledge and awareness between teachers who teach in areas prone to landslides and those who teach in areas that are not prone to landslides.